Is the Teaching Environment a Risk Factor for Depression Symptoms? The Case of Capricorn District in Limpopo, South Africa - Khomotso Comfort Maaga; Kebogile Elizabeth Mokwena (MDPI AG, 2023)
The global increase in mental disorders also identifies the workplace, including the teaching environment, as a key source of such disorders. Social problems among learners often put additional pressure on the teachers, over and above their normal academic, administrative and organizational responsibilities, thus contributing to high levels of stress among teachers. The purpose of this study was to determine the prevalence of depression symptoms, as well as the associated sociodemographic factors, among teachers in Capricorn District, Limpopo Province, South Africa. A cross-sectional quantitative study design using the Patient Health Questionnaire (PHQ-9) tool was used to determine the symptoms of depression among a sample of 381 teachers. A self-administrated questionnaire was used to collect sociodemographic data, which were analyzed descriptively. Pearson chi-square tests were used to explore associations between a range of sociodemographic variables and PHQ scores. A final logistic regression model was used for factors that were significantly associated with depression symptoms according to Chi-square tests. The majority of the participants were Black (83.45%) and female (70.87%) and had obtained a bachelor's degree as their highest qualification (53.95%). Almost half of participants (49.87%) tested positive for symptoms of depression, which ranged from mild to severe. Employment-related factors that were significantly associated with depression symptoms included the quintile ranking of the school, the school where employed, learner-to-teacher ratio and the subjects taught by the teacher. Personal factors that were associated with depression included gender, marital status and race. Depression symptoms amongst teachers were mostly associated with workplace factors.